Architectural Regionalism During the Neo-Classical Era: Classifying the Architectural “Hybrid” Stylistic Forms - Tengku Anis Qarihah Binti Raja Abdul Kadir; Norwina Mohd Nawawi (Cultural Syndrome, 2021)
Stylistic architectural changes that occurred during colonial era in South East Asian nations such as Malaysia and Indonesia, particularly in the 1800s had always been simplistically ‘lumped’ together as the colonial style. Using case studies of the Malay world, this paper argues, for the contrasting streams of public architecture; the modernized Malay Classical style; vs the Malayalised Colonial style; though they depict similar combinations of hybrid architectural tectonic language in buildings. This paper argues that various present writings and discourses had ‘hijacked’ the essentially evolving Malay style and had grouped these with the changes attributed to Colonial stylisations, rather than attributing them to the modernization of their own vernacular style. Using aristocratic buildings, the paper highlights cases with aim to expand the discourse on to include the evolving language of local Classical (Malay) architecture, which represent an evolvement from tradition to the Neo-Classical era of modernity. The missing discourse is characteristic of nation undergoing postcolonialism attributing to the rupture of history.  These essentially regionalized forms within the Neo-Classical era   are often mistaken as Colonial pastiche-like borrowings or ‘kitsch’ , rather than associating it within a broad local early modern vernacular which  arises local phenomena desire to modernize.